2021
DOI: 10.1111/jocn.15895
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salutogenesis‐based care on the sense of coherence in peritoneal dialysis patients

Abstract: Aims: This research is conducted to determine the effect of salutogenesis-based home care on the sense of coherence in patients with peritoneal dialysis.Background: Recent studies on the salutogenesis model have shown that the model is effective in promoting and improving health. It was observed that studies based on the salutogenesis model were carried out in the form of a training programme, and there was no study that shows its effectiveness on patient care by integrating it into the nursing process. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(47 reference statements)
2
3
0
1
Order By: Relevance
“…Our study highlights the SOC as a protective factor that can be influenced by therapeutic intervention, similarly to what has been performed in the context of other disorders [ 57 , 58 , 59 , 60 , 61 ]. In light of the research findings, there is a need to explore the ICF model in the context of ADHD, using longitudinal studies, based on the understanding that functional impairments, such as antisocial behavior, are possible products of a relation between ADHD symptoms and other protective factors.…”
Section: Discussionsupporting
confidence: 74%
“…Our study highlights the SOC as a protective factor that can be influenced by therapeutic intervention, similarly to what has been performed in the context of other disorders [ 57 , 58 , 59 , 60 , 61 ]. In light of the research findings, there is a need to explore the ICF model in the context of ADHD, using longitudinal studies, based on the understanding that functional impairments, such as antisocial behavior, are possible products of a relation between ADHD symptoms and other protective factors.…”
Section: Discussionsupporting
confidence: 74%
“…Our study points out the SOC, a protective factor that can be influenced by therapeutic intervention, similarly to what has been done in the context of other disorders (Jensen et al, 2016;Mayer & Boness, 2011;Odajima et al, 2017;Tan et al, 2015;Uzdil et al, 2021). In light of the research findings, there is a need to explore the ICF model further using a longitudinal study.…”
Section: Discussionsupporting
confidence: 79%
“…For example, it was found that targeted drug therapy for ADHD decreases antisocial behavior by 30-40% (Young & Cocallis, 2021;Retz et al, 2020). Other studies reported an interaction between ADHD and variables such as substance use and past arrest in predicting delinquent behavior (van der Maas et al, 2018;Breuer et al, 2020;García et al, 2021). Notably, these moderating variables are in themselves on the spectrum of antisocial behavior.…”
Section: Interaction In the Prediction Of Antisocial Behaviormentioning
confidence: 99%
“…It is highly plausible that enhancing SOC would result in a better QOL. Indeed, a recent pre-test–post-test control group experimental study among patients on peritoneal dialysis showed that salutogenesis-based care enhances the SOC and self-efficacy, provides symptom control, and decreases dialysis symptoms [ 26 ]. Specifically, through support therapy, psychologists are encouraged to listen, encourage, validate, and counsel.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the independent association between SOC and QOL in patients on hemodialysis was seldom investigated; previous efforts mainly focused on patients in pre-dialysis [ 25 ], or those receiving peritoneal dialysis [ 26 ], in general through correlational studies. Exploring this association is expected to generate knowledge with implications for clinical practice, particularly therapeutic interventions to enhance SOC, ultimately leading to improve QOL.…”
Section: Introductionmentioning
confidence: 99%